Influence of temperature and pressure on the electrical resistivity of gold and copper up to 1350 K and 100 GPa. (August 2020) - Hoc, Nguyen Quang; Tinh, Bui Duc; Hien, Nguyen Duc
Graphical abstract: Highlights: We develop a theory to investigate the pressure dependence of the electrical resistivity of Gold and Copper. The electrical resistivity of metals Au and Cu are calculated by using the statistical moment method. The numerical calculations will be performed up to a pressure of 100 GPa. Our results are compared with those of available experimental and theoretical data to verify the theory. Abstract: In this work, we have presented a new approach investigating the influence of temperature and pressure on the electrical resistivity of metals. In the framework of the statistical moment method, high temperatures up to 1350 K and high pressure up to 100 GPa electrical resistivity of Au and Cu are calculated. The equation of state, the Gruneisen parameter, and the Debye temperature of these metals are also discussed. The results show a good agreement with other theoretical calculations and the experimental data.